Effects of Non-Collagenous Proteins, TGF-β1, and PDGF-BB on Viability and Proliferation of Dental Pulp Stem Cells - Fahimeh Sadat Tabatabaei; Maryam Torshabi (eJournal of Oral Maxillofacial Research)
Objectives: The dentin matrix servers as a reservoir of growth factors, sequestered during dentinogenesis. The aim of this study was to assess the viability and proliferation of dental pulp stem cells in the presence of dentin matrix-derived non-collagenous proteins and two growth factors; platelet-derived growth factor BB and transforming growth factor beta 1.